De novo assembly and analysis of the transcriptome of Rumex patientia L. during cold stress. - Jianxin Liu; Yongqing Xu; Liguo Zhang; Wei Li; Zhenxue Cai; Fei Li; Mu Peng; Fenglan Li; Baozhong Hu (PLoS ONE, 2017)
Rumex patientia L. is consumed as a green vegetable in several parts of the world, and can withstand extremely low temperatures (-35°C). However, little or no available genomic data for this species has been reported to date. Here, we used Illumina Hiseq technology for transcriptome assembly in R. patientia under normal and cold conditions to evaluate how it responds to cold stress.After an in-depth RNA-Seq analysis, 115,589 unigenes were produced from the assembled transcripts. Based on similarity search analysis with seven databases, we obtained and annotated 60,157 assembled unigenes to at least one database. In total, 1,179 unigenes that were identified as differentially expressed genes (DEGs), including up-regulated (925) and down-regulated ones (254), were successfully assigned GO annotations and classified into three major metabolic pathways. Ribosome, carbon metabolism, oxidative phosphorylation and biosynthesis of amino acids were the most highly enriched pathways according to KEGG analysis. Overall, 66 up-regulated genes were identified as putatively involved in the response to cold stress, including members of MYB, AP2/ERF, CBF, Znf, bZIP, NAC and COR families.To our knowledge, this investigation was the first to provide a cold-responsive (COR) transcriptome assembly in R. patientia. A large number of potential COR genes were identified, suggesting that this species is suitable for cultivation in northern China. In summary, these data provide valuable information for future research and genomic studies in R. patientia.